Internet connectivity disruption in Turkey (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Turkey. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: TR-2026-0064. Severity: critical. Confidence: 75%